Encoding specificity principle (ESP) in enhancing motor memory performance skills / Muhammad Hafeez Basri - Basri, Muhammad Hafeez (2011)
Purpose This research studies the relationship between transfer of learning and motor movement on how a skill can be transferred, retained and produce consistency in performance by applying the theoretical principle in Encoding Specificity Principle (ESP). Methodology: Subjects selection based on the convenient sampling method. This method was used, as subjects in Universiti Pendidikan Sultan Idris (UPSI) were the least experience group in netball compared to other universities in Malaysia, thus satisfies the specific criteria that the researcher had set. Subjects was interviewed and involved in a shooting test before the researcher determines the grouping. Subjects were n= 40 (female) with age ranged between 20 - 25 years old, heights between 1.50m - 1.75m and weights between 40kg - 75kg. To ensure that useful and reliable data are collected, certain procedures are necessary in the collecting the data. The procedures was strictly adhered during the entire course of the study and classified as an experimental research. Subject was asked to perform two (2) tests. Pre and post-tests was conducted on every subject to determine their performance. The tests are specific visual aid training vs no specific visual aid training and specific verbal training instruction vs no verbal training instruction. The experimental group undergoes training (with a pre-determined training procedures) prior to the post-tests while the control group was not undergoing any predetermined training procedures. Results Paired Sample T-Test results showed that there was a significant difference in achievement for the treatment tests. In Test 1 (specific visual aid training test), the result was p-value (0.00), medium effect size (ES) of 0.5 and omega squared at 80%. In Test 2 (specific verbal training instruction test), the result was p-value (0.00), low effect size (ES) of 0.1 and omega squared at 80%. Therefore, all of the tests null hypotheses were rejected without creating Type 1 and Type 2 error. Findings The findings indicated that ESP had affected the performance of the subjects. These finding was consistent with the past studies, which indicates the transfer of learning principles in ESP were consistently able to show successful transfer rate. However, for future study purpose, studies in this area need to be conducted on athletes at high competitive level.